Intralesional bleomycin sclerotherapy for cystic hygroma in children - as alternative treatment - Sharanbasappa Gubbi; Sangmeshwar Patil; Chinmayee K. Reddy; J.C. Rajiv Reddy (Al Ameen Medical College, 2023)
Introduction: Although cystic hygromas can appear in any part of the body they are commonly found in the cervicofacial regions particularly in the posterior cervical triangle, axilla, mediastinum, groyne and below the tongue. The optimal treatment is total surgical excision; nevertheless, the mode of treatment is gradually shifting to sclrosant therapy. Keeping this point in mind, the present study focuses on usage of bleomycin as the sclerosant of choice in the treatment of cystic hygomas. Methods: A prospective study conducted in Mahadevappa Rampure Medcial College, Kalburagi, over a period of 2. Cystic hygroma was diagnosed clinically with radiological supplementation of Doppler ultrasonography or MRI. The procedure was performed under IV sedation and USG guidance. All patients received 3 doses of antibiotics 1 preoperatively and two post operatively. Number of doses of bleomycin was dependent on the prognosis and clinical evaluation. Results: Complete resolution without induration clinically seen in 16 out of 20 patients (80%), whereas good response was observed in 4 patients (20%) who had a repeat of the session after 3 months of the first session following which we attained complete resolution of the cystic hygroma. Side effects such as fever (15%) followed by fever along with erythema in 2 subjects (10%) and erythema in one subject (5%) were observed. Conclusion: In conclude, we recommend Intralesional Bleomycin Sclerotherapy as the primary method of treatment in cystic hygroma to avoid the risk of inadvertent damage from surgery and for cosmetic reasons.